Energy Consumption and Quality of Approximate Image Transformation - Damasevicius, R.; Ziberkas, G. (Elektronika ir Elektrotechnika, 2012)
The paper analyses a problem of effective image processing in mobile devices with limited resources. We analyse various approximate calculation methods for improving energy characteristics of components of image processing algorithms that are especially energy and CPU resource greedy. We research an image transformation applying the Twirl effect using data specialization (caching in look-up tables) and approximate computation of the trigonometric functions using Taylor series, Padé rational fractions and Chebyshev polynomials. Quality of transformed images is evaluated using standard image quality metrics. Based on the experimental results, the recommendations for mobile application developers are formulated. Ill. 8, bibl. 12, tabl. 1 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.120.4.1459